Complete genomic sequence of a Marinobacter species, a potential polyethylene degrader isolated from surface seawater - Iizuka, Ryo; Uemura, Sotaro (Microbiology Resource Announcements, 2024)
The bacterium sp. RI1 was isolated from surface seawater through an enrichment culture using low-density polyethylene as the sole carbon source. Herein, we report its complete genomic sequence. Genomic annotation revealed that the strain harbors the genes encoding enzymes involved in alkane degradation, thus supporting polyethylene degradation.